Una conversación con Robert Nozick acerca de Liberland = A conversation with Robert Nozick about Liberland (2017)
Robert Nozick's libertarian variant remains one of the most unique modern updates of liberalism. Through the recreation of a hypothetical interview, the American theorist engages here in a dialogue about the political constitution of Liberland, a no-man's land appropriated by Vít Jedlička and organized under the principles of libertarianism, the clarification of which is the purpose of this text. In the course of the conversation, comments and questions arise that allow further clarifications about the role of private property in this territory and its relation to negative liberty and justice; the necessity and form of political government; mechanisms of security and protection of freedoms; the place of political rights and taxation, among others, accompanied by a final reflection.